KEPASTIAN HUKUM DALAM ASPEK PERLINDUNGAN KONSUMEN TERHADAP INFORMASI KEAMANAN PRODUK DAN PENCANTUMAN LABEL KATEGORI PANGAN - Fitriana, Diana (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2023)
Law Number 8 of 1999 concerning Consumer Protection of the Republic of Indonesia explains that consumer rights include the right to comfort, security and safety in consuming goods and services. protection for consumers must be a serious concern by the government, especially for food products circulating in the community, so that consumers and society in general do not become victims of irresponsible producers. Business actors are prohibited from producing and/or trading goods and/or services as stipulated in Article 8 Paragraph (1) letter i UUPK, namely not placing labels or making descriptions of goods containing the name of the goods, size, net or net weight/content, composition, rules for use, date of manufacture, side effects, name and address of business actor and other information for use according to applicable laws and regulations. This study aims to find out how the consumer protection law is applied to expired food products and how to monitor and prevent expired food / food and beverage products circulating in the community. To support this research, data collection techniques were used in the form of interviews and literature studies. The results of the study show that the application of consumer protection laws has not been carried out optimally where entrepreneurs as providers of goods and services pay less attention to their obligations and consumer rights as well as the community does not pay much attention to their rights as consumers. The role of BBPOM towards consumers and guidance to business actors is a form of legal protection for the community through the process of outreach, guidance, inspection and supervision of the distribution of food products circulating at consumer shopping centers or facilities. Keywords: Food Safety, Label, Legal Certainty